Facilitation of Non-Formal Education for Families at Risk of Stunting Through Mobilization of Family Planning Instructors - Putra, Yuda Ganda; Yuhana, Yuyu; Fafilaya, Chathiyana; Kurniatin, Epong (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Stunting is the government's main concern issue at the moment. The impact of stunting is not only related to health factors, both physical and cognitive, but can result in multidimensional problems. Various efforts have been made by the current government to anticipate the real threat of stunting which is still quite high in Indonesia. One effort that can be made is to optimize the role of family planning instructors as educators in non-formal family education, namely by facilitating non-formal education for families at risk of stunting through the mobilization of family planning instructors. This article is the result of descriptive analysis based on a qualitative approach. The research results show that the mobilization of family planning instructors to increase maternal knowledge and good parenting patterns, as well as health education through IEC about stunting, for mothers from families at risk of stunting, is very important to reduce the prevalence of stunting in toddlers, especially in villages where stunting is located. Optimizing the role of family planning instructors so that they are effective is implemented by making instructors as educators, mentors/companions, motivators and communicators for families at risk of stunting. On the other hand, so that family planning instructors can reach remote rural areas and provide informal education directly to families at risk of stunting, this can be done through changes to the Mobile Information Units at BKKBN Representatives.